2015
DOI: 10.1074/jbc.m114.584524
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of BamB Bound to a Periplasmic Domain Fragment of BamA, the Central Component of the β-Barrel Assembly Machine

Abstract: Background:The ␤-barrel assembly machine (BAM) is essential for outer membrane protein (OMP) biogenesis and Gram-negative bacterial survival. Results: BamB binds polypeptide translocation-associated domain 3 (POTRA3) of BamA. Conclusion: BamB, binding at the hinge in the periplasmic domain of BamA, is poised to modulate BAM conformational changes. Significance: The BAM complex architecture illuminates the mechanism of OMP assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…BamB is known to bind to BamA (37,71), and a crystal structure of a BamB-POTRA3-5 fragment complex (71) in addition to recent crystal structures of the BamA/B/C/ D/E complex (39,40) show that the BamB b-propeller contacts the face of the POTRA3 b-sheet. For BamD, the only essential BAM lipoprotein (29), a crystal structure of a BamD-POTRA4-5 fragment identified the interface structural elements between subunits (33) and this interface has been confirmed in crystal structures of the BAM complex (38)(39)(40).…”
Section: Binding Of Bamb and Bamd Is Compatible With Selected Conformmentioning
confidence: 94%
“…BamB is known to bind to BamA (37,71), and a crystal structure of a BamB-POTRA3-5 fragment complex (71) in addition to recent crystal structures of the BamA/B/C/ D/E complex (39,40) show that the BamB b-propeller contacts the face of the POTRA3 b-sheet. For BamD, the only essential BAM lipoprotein (29), a crystal structure of a BamD-POTRA4-5 fragment identified the interface structural elements between subunits (33) and this interface has been confirmed in crystal structures of the BAM complex (38)(39)(40).…”
Section: Binding Of Bamb and Bamd Is Compatible With Selected Conformmentioning
confidence: 94%
“…In addition to BamA, the BAM complex is composed of several lipoproteins (BamB/C/D/E (7-10)). It is described that the third POTRA domain of BamA binds BamB (11) and thus is involved in complex formation. In turn, the first, and thus most N-terminal, POTRA domain is an essential interaction partner of SurA, which has been proposed to deliver b-barrel proteins from the plasma membrane to the BAM complex (12).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the lateral gate , Noinaj et al, 2013a conformational change simulated for BamA was also suggested for LptD (Dong et al, 2014). The BAM exists as a BamAB and BamACDE protein complex (Sklar et al, 2007a, Malinverni et al, 2006, Hagan et al, 2010, Jansen et al, 2015a. However, LptE differs from BamB in structure, size (BamB: 40KDa, LptE: 20KDa), and location in relation to the central protein component.…”
Section: Growth Characteristics Of Mg1655 Periplasmic Chaperone Mutanmentioning
confidence: 86%
“…BamA is the major protein that catalyses folding of OMPs and can act alone or in complex with either BamB or with BamC, BamD and BamE (Malinverni et al, 2006, Kim et al, 2007, Hagan et al, 2010, Plummer and Fleming, 2015. The Cterminal domain of BamA forms a transmembrane 16-stranded β-barrel core, while the Nterminal region of BamA forms five soluble periplasmic polypeptide-transport-associated domains (POTRA) (Jansen et al, 2015b, Kim et al, 2007, Gatzeva-Topalova et al, 2010, Gatzeva-Topalova et al, 2008. These POTRA domains contribute to BamA stability and directly interact with BamBD within the periplasm, nascent polypeptides and the periplasmic chaperone SurA (Bennion et al, 2010, Kim et al, 2007, Workman et al, 2012, Dong et al, 2012a.…”
Section: The β-Barrel Assembly Machine (Bam) Complexmentioning
confidence: 99%
See 1 more Smart Citation